Refining the relationship between entrepreneurial skills and start-up-behavior: The role of fear of failure and age-based self-image - Muhammad Yasir; Muhammad Yasir; Abdul Majid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
This study provides information about how entrepreneurial skills (pro-activity, risk tolerance, and creativity) affect start-up-behavior. This study integrates entrepreneurial skills as an important aspect to the proposed model based on Ajzen's theory to establish intention-behavior link. Furthermore, fear of failure and age-based self-image are featured as negative aspects in this model to explore how these two factors deteriorate intention-behavior link. Data were collected from owner/managers of SMEs in Pakistan. Descriptive statistics, moderated hierarchical regression and structural equation modeling (SEM) approach were used for the purpose of analysis. The findings revealed that entrepreneurial skills have a positive relationship with perceived behavior control, subjective norms, and personal attitude. Furthermore, results of the study showed that perceived behavior control, subjective norms, and personal attitude also have positive relations with start-up intentions leading to start-up behavior. Moreover, the results suggested a negative moderation effect of fear of failure and age-based self-image on intention-behavior link.
Keywords: 330; entrepreneurial skills; start-up intention; fear of failure; start-up behavior; subjective norms; personal attitude; and perceived behavior control